Organ Procurement Organization Survey of Practices and Beliefs Regarding Prerecovery Percutaneous Liver Biopsy in Donation After Neurologic Determination of Death. Issue 4 (April 2017) - Oliver, Joseph Benton; Marcus, Andrea Fleisch; Paster, Mark; Nespral, Joseph; Bongu, Advaith; Dikdan, George; Brown, Lloyd; Neidlinger, Nikole; Koneru, Baburao
Abstract : Background: Prerecovery liver biopsy (PLB) allows histological evaluation of the organ before procurement. The opinions and what factors might influence PLB use within Organ Procurement Organizations (OPOs) are unknown. Methods: A survey instrument was distributed by the Association of OPOs to the clinical directors of all 58 OPOs. Descriptive statistics were calculated. Results were also stratified based on OPO characteristics. Results: Forty-nine (84.5%) of 58 OPOs responded to the survey; 40 (81.6%) of 49 currently perform PLB. This did not vary based on land mass, population, livers discarded, transplanted, donor age, or recipient MELD scores. Donor age, obesity, alcohol abuse, hepatitis serology, liver only donor, imaging results, and transplant center request were the most common indications for PLB in over 80% of OPOs. The median rate of performance is 5% to 10% of donors. Most use interventional radiologists to perform and the donor hospital pathologist/s to interpret PLB. Most OPOs believe PLBs are safe, reliable, useful, and performed often enough. Most say they did not believe they are easy to obtain. Beliefs were mixed regarding accuracy. The topics likely to influence PLB use were utility and accuracy of PLB, and availability of staff to perform PLB. OPOs that perform PLB more often were more likely to have favorable opinions of safety and pathologist availability, and more influenced by safety, reliability, availability, and a national consensus on the use of PLB. Conclusions: Considerable variability exists in the use of PLB. Additional information on the utility, accuracy, and safety of PLB are needed to optimize its use. Abstract : This work collected data from 49 organ procurement organizations regarding the use of prerecovery liver biopsies in potential organ donors and finds that there is wide variability regarding indications and logistics. The more difficult questions of whether these biopsies enable more donations and their predictive accuracy require further study. Supplemental digital content is available in the text.